Secondary aluminated mesoporous molecular sieves AI-MCM-41 : synthesis, characterization and catalytic activity - 604322 Salasiah Endud (Skudai : Universiti Teknologi Malaysia, 1999)
Thesis (PhD) - Universiti Teknologi Malaysia, 1999